Used Motorcycle Transactions via Facebook: A Comparative Study of Islamic Law and Consumer Protection - Muhammad Fajar; Ahmad Musadad; Hammam Hammam; Khoirun Nasik; Umi Indasyah Zahro (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The phenomenon of online buying and selling through social media, particularly Facebook, has experienced significant growth and has become a popular alternative for used motorcycle transactions, including in the Kwanyar area of Bangkalan. However, this buying and selling practice poses several problems, such as a lack of clarity regarding contracts, incomplete or misleading vehicle information, and potential losses for consumers. This study aims to analyze the practice of buying and selling used motorcycles in the Kwanyar Facebook group from the perspective of Islamic law and Indonesian consumer protection law. This study used a qualitative approach with a case study method. Data collection techniques were conducted through observation, interviews with the sellers and buyers, and documentation of transaction activities in the Facebook group. The results indicate that the buying and selling practice is generally valid according to sharia due to the fulfillment of the contract elements and efforts to avoid serious gharar. However, there is still a lot of non-disclosure of information from sellers, which has the potential to violate consumer rights as stipulated in the Consumer Protection Law. Therefore, education and supervision are important to ensure that online buying and selling practices align with the principles of fairness, transparency, and legal protection.